Analysis of Circular RNA Expression Profile in HEK 293T Cells Exposed to Ionizing Radiation. Issue 2 (4th January 2019) - He, Ningning; Sun, Yuxiao; Yang, Mengmeng; Lu, Qianying; Wang, Jinhan; Xiao, Changyan; Wang, Yan; Du, Liqing; Ji, Kaihua; Xu, Chang; Liu, Qiang
Radiation therapy is one of the most common cancer treatments. It is important to understand how cells respond to ionizing radiation (IR) to improve therapeutic efficacy. Circular RNAs (circRNAs) recently have been found to regulate a variety of cellular processes. However, it is poorly defined that their expression pattern and their identity in cells following IR exposure. Here, we performed high-throughput sequencing and comprehensive analysis of circRNA expression in human embryonic kidney (HEK) 293T cells before and after irradiation. We identified totally 5592 circRNAs and discovered 1038 new circRNAs. We found 158 circRNAs with significantly differential expression after IR exposure. Among them, there were 61 upregulated and 97 downregulated circRNAs. Using Gene Ontology, Kyoto Encyclopedia of Genes and Genomes pathway, and circRNA-microRNA-messenger RNA network analyses, we found the differentially expressed circRNAs might be involved in the signal pathways of oxidative phosphorylation, epithelial growth factor receptor (EGFR) tyrosine kinase inhibitor resistance, and mammalian target of rapamycin (mTOR) signaling.